1991 LAS VEGAS CONVENTION PROGRAM OUTLINE. (Reading Teacher)
Presents an outline of the 36th Annual International Reading Association Convention Program, which will be held in Las Vegas, Nevada on May 6-10, 1991. Cosponsored meeting; Exhibitions; Award presentations.